OPTIMIZING STUDENT ENGAGEMENT AND SCIENCE LEARNING OUTCOMES THROUGH THE COOPERATIVE LEARNING MODEL OF MAKE A MATCH TYPE - Lisa, Lusiana; Adi, Banu Setyo (Universitas Tanjungpura, 2026)
Abstract This study aimed to improve engagement and learning outcomes in Science among fifth-grade students through the implementation of the Make a Match cooperative learning model. Classroom action research was conducted over two cycles using the Kemmis and McTaggart model, involving eight students as participants. Data were collected through observation to assess student engagement and learning process achievement, as well as tests to measure learning outcomes, and analyzed using descriptive quantitative methods. The results indicated significant improvements, with learning achievement increasing from 79.76% in the first cycle to 95.80% in the second cycle, student engagement reaching 87.5% in the “good” category, and all students (100%) meeting the minimum mastery criteria for Science learning outcomes by the end of the second cycle. These findings demonstrate that the Make a Match model effectively fosters an interactive and enjoyable learning environment, enhancing both active participation and academic achievement, suggesting that cooperative learning models can serve as a viable alternative to address low engagement and Science learning outcomes in elementary schools. Keywords: Learning outcomes, make a match, student engagement Abstrak Penelitian ini bertujuan untuk meningkatkan keterlibatan dan hasil belajar IPA pada siswa kelas lima melalui penerapan model pembelajaran kooperatif tipe Make a Match. Penelitian tindakan kelas dilaksanakan dalam dua siklus menggunakan model Kemmis dan McTaggart, dengan delapan siswa sebagai peserta. Data dikumpulkan melalui observasi untuk menilai keterlibatan siswa dan pencapaian proses belajar, serta melalui tes untuk mengukur hasil belajar, kemudian dianalisis menggunakan metode deskriptif kuantitatif. Hasil penelitian menunjukkan adanya peningkatan yang signifikan, dengan pencapaian belajar meningkat dari 79,76% pada siklus pertama menjadi 95,80% pada siklus kedua, keterlibatan siswa mencapai 87,5% pada kategori “baik,” dan semua siswa (100%) memenuhi kriteria ketuntasan minimum hasil belajar IPA pada akhir siklus kedua. Temuan ini menunjukkan bahwa model Make a Match secara efektif menciptakan lingkungan belajar yang interaktif dan menyenangkan, meningkatkan partisipasi aktif serta prestasi akademik siswa, sehingga model pembelajaran kooperatif dapat menjadi alternatif yang layak untuk mengatasi rendahnya keterlibatan dan hasil belajar IPA di sekolah dasar. Kata Kunci: Hasil belajar, make a match, keaktifan